Wellbeing : policy and practice - Knight, Anneyce; La Placa, Vincent; McNaught, Allan, 1952- (Banbury, UK : Lantern, 2014)
This text details the contemporary research evidence base for health and wellbeing within the global context and discusses how this improved knowledge can be applied to both healthcare policy and practice.
Bibliography : pages 115-134.
Keywords: Health; Well-being.